2014
DOI: 10.1128/cvi.00609-14
|View full text |Cite
|
Sign up to set email alerts
|

Field Evaluation of the InBios Chagas Detect Plus Rapid Test in Serum and Whole-Blood Specimens in Bolivia

Abstract: h Trypanosoma cruzi causes Chagas disease, which affects an estimated 7 million to 8 million people. Chagas disease is endemic throughout Latin America, with the highest prevalence in Bolivia. Conventional diagnosis requires a well-equipped laboratory with experienced personnel. We evaluated the Chagas Detect Plus (CDP) (InBios, Seattle, WA), a rapid immunochromatographic assay for IgG antibodies to T. cruzi. CDP performance was compared to infection status based on results obtained by indirect hemagglutinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
44
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 18 publications
6
44
2
Order By: Relevance
“…This, coupled with the high FOI estimate, demonstrates significant recent vector transmission. Although the specificity of the CDP (91.9%) in this study was lower than that reported in previous analyses, screening in this rural village was greatly facilitated by the use of this rapid test (Eguez et al, 2017;Shah et al, 2014). Pairing a highly sensitive rapid test with a more specific confirmatory test allows efficient screening, even in a challenging community setting.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…This, coupled with the high FOI estimate, demonstrates significant recent vector transmission. Although the specificity of the CDP (91.9%) in this study was lower than that reported in previous analyses, screening in this rural village was greatly facilitated by the use of this rapid test (Eguez et al, 2017;Shah et al, 2014). Pairing a highly sensitive rapid test with a more specific confirmatory test allows efficient screening, even in a challenging community setting.…”
Section: Discussioncontrasting
confidence: 59%
“…Children were screened using the Chagas Detect Plus (CDP) immunochromatographic assay (InBios International, Inc., Seattle, WA, USA). This assay has previously been shown to have sensitivity of 96.2% and specificity of 98.8% in a similar population in the Bolivian Chaco (Shah et al, 2014). Children with positive CDP results had venous blood drawn and tested by indirect haemagglutination assay (IHA) (Chagas Polychaco kit; Lemos Laboratories, Buenos Aires, Argentina) following national Chagas disease control protocols.…”
Section: Screeningmentioning
confidence: 99%
“…Therefore, in full agreement with others, RDTs must be field validated in each particular site before its use for screening is recommended [19,20]. Seroprevalence detected in this work was quite high (60.8%), but accordingly to the Bolivian government Chagas Management Departmental Program (with data from 2013), Chagas disease seroprevalence in the department of Chuquisaca was estimated to be 5.6% amongst children between 1–4 years old, 5.4% in the age range from 5 to 14 years old, and 56.6% in those ≥15 years old [23].…”
Section: Discussionmentioning
confidence: 92%
“…Relatively few studies reported data on CD epidemiology in the Bolivian Chaco, although it is acknowledged as one of the most affected areas in the planet. In Table 2, we report a summary of the main available studies concerning anti-T. cruzi antibodies seroprevalence in the human population of the Bolivian Chaco [9][10][11][12][13]. A detailed and accurate analysis of the epidemiological evolution is challenging, being hindered by several limitations.…”
Section: Discussionmentioning
confidence: 99%